Odpowiedzi

2010-04-15T15:10:07+02:00
A)
0,2x+ 0,3= -0,5
0,2x=-0,5-0,3
0,2x=-0,8
x=-4


b)
0,4+ 0,25x = -2
0,25x=-2-0,4
0,25x=-2,4
x=-9,6


c)
2,1 - 0,3x = 0,4x
-0,3x-0,4x=-2,1
-0,7x=-2,1
x=3


d)
-1,5x -3 = 0,2x + 6
-1,5x-0,2x=6+3
-1,7x=9
x=-5⁵/₁₇
1 5 1
2010-04-15T15:14:36+02:00
A) 0,2x + 0,3= -0,5
0,2x = -0,5-0,3
0,2x = -0,8/:0,2
x=-4

b)0,4+0,25x=-2
0,25x=-2-0,4
0,25x=-2,4/ :0,25
x=-9,6

c)2,1-0,3x=0,4x
-0,3 - 0,4x = -2,1
-0,7x = -2,1 /:(-0,7)
x= 3

d)-1,5x - 3 =0,2x + 6
-1,5x-0,2x = 6+3
-1,7x = 9 /: (-1,7)
x = -5 5/17
1 5 1